PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR AL QUR’AN HADIS MATERI PENGEMBANGAN ILMU PENGETAHUAN DAN TEKNOLOGI - MASMUKHAH MASMUKHAH (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2022)
The use of lecture and question and answer methods in conventional Qur'an Hadith subjects is less effective, so students are less interested in participating in learning materials. There is a tendency for less than optimal learning outcomes. This study aims to improve learning outcomes in the subjects of the Qur'an Hadith material development of science and technology through the application of the best learning problem learning model. This type of research is Classroom Action Research (CAR). This research was conducted at MAN 1 Jembrana Bali, the research subjects were students of class XII IPS 1, the number of students was 32 people. In this study, two cycles were carried out. The source of data in this study is quantitative data from student scores taken at the end of each cycle. The results showed that the level of mastery learning in the first cycle was 71.88%, while in the second cycle it was 84.38%. There is an increase in the percentage of complete learning 18.75% from pre-cycle to cycle I, and 12.5% ??from cycle I to cycle II. The class average in Cycle I was 75.78. While in the second cycle 83.44. There was an increase in class average of 6.09 points from pre-cycle to cycle I, and 7.66 points from cycle I to cycle II. The best learning problem learning model can improve learning outcomes of the Qur'an Hadith in the development of science and technology. ABSTRAKPenggunaan metode ceramah dan tanya jawab pada mata pelajaran al Qur’an hadis secara konvensional kurang efektif, sehingga siswa kurang berminat dalam mengikuti materi pembelajaran. Terdapat kecenderungan hasil belajar kurang maksimal. Penelitian ini bertujuan untuk meningkatkan hasil belajar pada mata pelajaran al Qur’an Hadis materi pengembangan ilmu pengetahuan dan teknologi melalui penerapan model pembelajaran problem best learning. Jenis penelitian ini adalah penelitian Tindakan Kelas (PTK) Penelitian ini dilakukan di MAN 1 Jembrana Bali, subyek penelitian adalah siswa kelas XII IPS 1, jumlah siswa 32 orang. Pada penelitian ini dilakukan dua siklus. Sumber data pada penelitian ini adalah data kuantitatif dari nilai siswa yang diambil pada tiap akhir siklus. Hasil penelitian menunjukkan bahwa tingkat ketuntasan belajar pada siklus I adalah 71,88 %, Sedangkan pada siklus ke II adalah 84,38 %. Terdapat peningkatan prosentase ketuntasan belajar 18,75 % dari pra Siklus ke siklus I, dan 12,5 % dari siklus I ke siklus II. Rata-rata kelas pada Siklus I 75,78. Sedangkan pada siklus II 83,44. Terdapat peningkatan rata-rata kelas 6,09 point dari pra siklus ke siklus I, dan 7,66 point dari siklus I ke siklus II. Model Pembelajaran problem best learning dapat meningkatkan hasil belajar al Qur’an Hadis pada materi pengembangan ilmu pengetahuan dan teknologi.